Educação superior a distância no Brasil : análise descritiva das características socioeconômicas dos alunos do EAD pelo viés do ENADE (2011-2019) - Soligo, Eduarda Pinto (2021)
Distance Education (DE), a modality of education carried out through the intense use of information and communication technologies, where teachers and students are physically separated in space and/or time, is growing and expanding more and more in the field of Higher Education. In this context, this work desired to study concepts that underlie the modality of distance education, to highlight some historical marks for the consolidation of the current Distance Education (DE) in Brazil and in the World, as well as to trace the socioeconomic profile of students and institutions of this type of education. The DE is growing globally and in Brazil the profile is also growing. The first evidence in Brazil of DE can be found between the XVIII and XIX centuries, and today presents an acceptance throughout the National Territory. The dynamics of the expansion of DE in Brazil is marked by several characteristics, including the concentration of enrollment in the same undergraduate courses and the advancement of the private sector. The most sought-after courses are the higher courses of the bachelor's degrees and the concentration areas are located in the southern region of the country. The students of this modality, mostly, are female, on average 40% self-declared white and are between 31 and 50 years old, profiling adult students. These students have other types of responsibility, such as family composition with spouses and/or children and family income on average of up to 3 minimum wages (R$ 1,431.01 to R$ 2,862.00). The most developed countries already live a more advanced reality of DE than in Brazil, but the results suggested that the Brazilian growth of this modality follows the international profile: the country has growth potential in the sector, because despite the difficulties, the sector continues to grow constantly. Due to the good results of acceptance of DE, this follow-up proves to be valuable for future investments, DE presents itself as a relevant tool in the process of democratization of education in Brazil.